Performance-Based Funding of Universities in Europe - Estermann, Thomas; Claeys-Kulik, Anna-Lena (International Higher Education, 2016)
Performance-based funding of universities is often perceived as a useful tool by policy makers, both to increase the transparency of public spending by linking it to measurable indicators, as well as to incentivize and reward the achievement of certain policy goals. However, the analysis reveals that the expectations towards performance-based funding are often too high and that it should be used with caution due to the various effects that are difficult to control.